Perancangan Tekstil Burung Hong dan Bunga Meihua pada Cheongsam Modern dengan Teknik Sublim Printing - Devinta, Nathasya Alin; Dartono, Felix Ari (Universitas Negeri Surabaya, 2024)
Indonesia and China have been closely related since ancient times. The purpose of this design was the development of two-cultural acculturation motifs that were applied in a fashion design work that gave rise to a new, unique and meaningful blend of motifs, as well as education to the public about cultural acculturation.This method of design uses an approach in the creation of artwork according to Bram Palgunadi (2008). The approach has three main processes: exploration, extraction and termination.The result of this design was an exploration of motifs that resulted in a new motif combining the Hong Bird and the Meihua Flower. Visualization of this motif is applied in fashion products, namely Cheongsam / traditional women's clothing in modern China. The technique used to realize this product is batik printing. The colors used are those commonly used in Chinese culture in fashion products such as red, green, and blue, where each color has its own meaning and philosophy.